A representação social de moradores do entorno das escolas rurais paralisadas/extintas no municipio de Almirante Tamandaré – PR - Borges, Vanusa Emilia (2016)
The closure of rural schools is ravaging the country in almost all regions and this is not different in Paraná, and either in the Metropolitan Region of Curitiba, where there are already 113 schools closed. In the city of Almirante Tamandaré, local of our research, we were closed 9 of 13 rural public schools in the municipality. There are numerous initiatives that show that closing schools is crime. Considering these aspects, defined a general objective to analyze the impacts of the closure of rural municipal schools in the city of Almirante Tamandaré by the Social Representation of residents. The research subjects are nine residents of the surrounding communities of rural schools closed in the municipality. The analyzes were developed in light of the theory of social representations (Moscovici, 2013). The results show that closing schools brings negative impacts to communities, such as loss of references, invisibility and loss of identity ofcommunities. Residents say they heard school closure, with short notice and that communities have failed to mobilize the time and silenced it. Even upset, live now, with public buildings abandoned, with empty schools closed, worried about their children who are forced to travel long distances to school transport, away from their communities. Despite the revolt of the residents, only one community, even having spent nine years of school closure, they are mobilizing to try to reopen the school, because of the importance of the social function of this for the residents.